COHERENCE AND COHESION IN THE INSTRUCTIVE TEXTS OF CHINESE BUN RECIPES - Yulie Neila Chandra; Gustini Wijayanti; C. Dewi Hartati; Hin Goan Gunawan (Bambuti, 2022)
This article describes coherence and cohesion in the instructive (procedural) text of Chinese bun recipes. This paper aims to explain the coherence of meaning and form in the instructive text. By adhering to the view of positivism, the study used methods of content analysis and variation analysis of discourse, focusing on structural categories in the text, including forms and meanings in clauses. The coherence of meaning and form in the instructive text of bun recipes is interrelated. The coherence of meaning indicates the relations of parallels between instructions, expressed by verbs, and also result in a chronological relation, expresses successive and progression. There is no contradiction in the instructions. In this instructive text of the Chinese bun recipes, there is also an individual identity as a coherence marker, refers to the concept of buns skin and buns filling. Grammatical cohesion is showed by anaphoric references, subject ellipsis, and conjunctions of succesive relation. Lexical cohesion is indicated by reiteration, namely repetitions, such as noun, verb, preposition, and conjunction. Reiteration is also expressed by synonyms such as verb, preposition, and conjunction synonyms, as well as hyponyms and hyperonyms expressed by the inclusion of meaning in the ingredients for making buns.